Strategies In Teaching English Reading To Visually-Impaired Student - Hesti Kartikasari; Riski Lestiono (Universitas Brawijaya, 2017)
Reading is really challenging for visually-impaired students, compared to other skills. The visually-impaired students learn reading skill in a different manner from the majority of students, such as they use Braille book and auditory media due to their inabilities to accommodate the visual teaching media. The visually-impaired students are required to be taught by means of specific strategies. Accordingly, it is of urgency to study further deeper how reading skill is taught in SMA-LB Negeri Pembina Lawang. The specific purposes of this study were describing the strategies used by English teacher, describing the problem faced by English teacher, and explaining how the English teacher solved the problem in teaching reading to the visually impaired student. The qualitative research design was employed in this study. The instruments used were observation checklist, field notes, and interview guide. It is found that there were six strategies used by English teacher in teaching reading to the visually impaired student, namely: (1) identifying the purpose of a text, (2) skimming the text for main ideas, (3) scanning the text for specific information, (4) analyzing the vocabulary, and two other strategies shown by the use of media suchlike (5) e-text strategy and (6) auditory strategy. There were five problems along with the ways to overcome the problems (1) English teacher could not use game-based strategy; (2) the English teacher had difficulty to introduce new vocabulary, but then the English teacher explained it clearly in other ways; (3) the English teacher could not use interactive teaching strategy because the visually impaired student was only one; (4) the English teacher had problem in time management, but then the English teacher gave additional time to teach visually impaired student; and (5) the English teacher had problems in implementing e-text strategy to the visually impaired student because the student had difficulty in understanding the dialect of native speaker (the voice of computer), but the English teacher let the visually impaired student get accustomed to that native like voice.Key Words: Teaching Reading, Teaching Reading Strategies, Visually-Impaired Student